Enhancing Early Childhood Cooperative Play Skills Through a Social Intervention Program - Sianipar, Riko; Komba, John (Journal of Early Childhood Education and Teaching (JECET), 2025)
Purpose – This study aims to assess the impact of a social intervention program on enhancing cooperative play skills among early childhood learners. Cooperative play is essential for promoting children’s social, emotional, and behavioral development, including responsibility, teamwork, and interaction with peers and others.Design/methods/approach – The study adopted a quantitative approach with an experimental design. Data were collected through role-play activities embedded within a social intervention program. The research involved early childhood learners, and their social behaviors—such as cooperation and responsibility were assessed using structured online questionnaires via Google Forms. The results were analyzed using statistical methods, including T-tests conducted in SPSS.Findings – The findings indicate a significant improvement in cooperative play skills after participating in the social intervention program. Children demonstrated increased collaboration, a stronger sense of responsibility, and improved social interaction. The program effectively fostered social competencies and emotional awareness among early childhood learners.Research implications/limitations – The study is limited to a specific group of early childhood learners and a short intervention period. Future studies should consider a longer intervention duration, larger sample sizes, and diverse educational settings to ensure broader applicability of the findings.Originality/value – This research highlights the value of structured social intervention programs in early childhood education. It provides practical implications for educators and caregivers aiming to cultivate children's social skills through meaningful, developmentally appropriate play-based strategies.